2016
DOI: 10.5194/bg-13-2715-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light on photosynthetic efficiency of sequestered chloroplasts in intertidal benthic foraminifera (<i>Haynesina germanica</i> and <i>Ammonia tepida</i>)

Abstract: Abstract. Some benthic foraminifera have the ability to incorporate functional chloroplasts from diatoms (kleptoplasty). Our objective was to investigate chloroplast functionality of two benthic foraminifera (Haynesina germanica and Ammonia tepida) exposed to different irradiance levels (0, 25, 70 µmol photon m −2 s −1 ) using spectral reflectance, epifluorescence observations, oxygen evolution and pulse amplitude modulated (PAM) fluorometry (maximum photosystem II quantum efficiency (Fv/Fm) and rapid light cu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 61 publications
2
71
0
1
Order By: Relevance
“…(1.8-2.0) indicates a primary consumer at a low irradiance (Table 2; Figure 2a). Furthermore, kleptoplast-bearing foraminifera can maintain kleptoplasts functionally for certain periods without the kleptoplast's dividing (Correia & Lee, 2002;Grzymski, Schofield, Falkowski, & Bernhard, 2002;Jauffrais et al, 2016;Lopez, 1979 Figure 2a,b).…”
Section: Effectofendobioticmicroalgaeon Foraminiferaltrophicfunctionmentioning
confidence: 99%
“…(1.8-2.0) indicates a primary consumer at a low irradiance (Table 2; Figure 2a). Furthermore, kleptoplast-bearing foraminifera can maintain kleptoplasts functionally for certain periods without the kleptoplast's dividing (Correia & Lee, 2002;Grzymski, Schofield, Falkowski, & Bernhard, 2002;Jauffrais et al, 2016;Lopez, 1979 Figure 2a,b).…”
Section: Effectofendobioticmicroalgaeon Foraminiferaltrophicfunctionmentioning
confidence: 99%
“…germanica and Elphidium williamsoni had a net uptake of inorganic carbon (H 14 CO 3 ) in light, and experiments with oxygen microelectrodes demonstrated that maximal O 2 production by H . germanica depended on light intensity and light history 11 , 23 . A kleptoplastic strategy thus provides these organisms with both carbon and a source of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…(d) Diversity of gene products from communities of eukaryotic excavate symbionts in termite guts reflects the environment of their host communities (Duarte, Nobre, Borges, & Nunes, 2018); (e) Hermatypic coral are dependent on the dinoflagellate Symbiodinium for 95% of their energy (Gilbert et al, 2010). (f) Acanthamoebae host amoeba-resistant bacteria like Legionella pneumophila, which have evolved to resist digestion and in some cases even to survive within human macrophages (Greub & Raoult, 2004;Loret & Greub, 2010); (g) Ciliate Paramecium tetraurelia hosts bacteria Caedibacter taeniospiralis in its cytoplasm that can kill non-host P. tetraurelia and protect current hosts from its killer mechanism (Grosser et al, 2018); (h) Single-cellular foraminifera can "steal" chloroplasts from the diatoms and other algae they eat to use for photosynthesis-a phenomenon known as kleptoplasty (Clark et al, 1990;Jauffrais et al, 2016); (i) the parasitic wasp Asobara tabida needs Wolbachia bacteria to develop into adulthood and form its ovaries properly (Gilbert et al, 2010). (j) Acrythosiphon pisum, otherwise known as pea aphids, need gene products from the endosymbiotic bacterium Buchnera aphidicola to make essential amino acids it does not get from its diet of sap (Wilson et al, 2010) bacteria in pea aphids gained a gene cluster from another endosymbiont, Cardinium or Rickettsia, through lateral gene transfer (Nikoh et al, 2014).…”
Section: Hologenomes: a Spectrum Of Intimacymentioning
confidence: 99%
“…Host ( (2011) Amoebozoa Acanthamoeaba Diverse bacteria Greub and Raoult, (2004) and Loret and Greub, (2010) Neoparamoeba sp Perkinsela sp. (Excavata) Nowak and Archibald (2018) Rhizaria Foraminifera Dinoflagellates, diatoms Jauffrais et al (2016) and Pillet et al (2011) Alveolata Paramecium tetraurelia Caedibacter taeniospiralis Grosser et al (2018)…”
Section: Host Cladementioning
confidence: 99%